Ang prinsipeng duwag - Reyes, Severino O.; Bellen, Christine S.; de Jesus, Ruben (Pasig City: Anvil Publishing House, 2005)
A retelling of the story about a cowardly prince who tried everything to avoid leading a war. In the end, through his love for the princess, the prince was able to overcome his fear.
Primary
Keywords: Folk literature, Philippine (Filipino); Cowardice -- Juvenile fiction